Tracking The Source of Antimicrobial Production From House Fly (Musca domestica): Right-Wing of Fly Or Gut System? - A Mini-Review - Muhammad Asril; Ika Agus Rini; Indah Oktaviani; Mushaliyah Mushaliyah (Elkawnie, 2021)
Abstract: The house fly (Musca domestica) is a vector of disease-causing bacteria because of its habit of perching and feeding on various substrates of pathogenic bacteria.  His role as a disease carrier contradicts the hadith narrated by Bukhari, which is "If a fly falls into your vessel, drown it and then remove it because one of its wings carries disease and the other is the cure". This hadith indicates the presence of antimicrobial compounds produced from the body of flies. Various research reports show that the truth of this hadith is that there are antimicrobial-producing bacterial symbionts on the wings of flies (left and right) that can kill pathogenic bacteria on one of the wings or both. Antimicrobial compounds are also produced naturally in the digestive tract of flies from the larval stage to adulthood as a response to the body's defense against the presence of pathogenic bacteria in their bodies. The antimicrobial compounds are lysozyme, defensin, cecropin, diptericin, and several antimicrobial peptide compounds. This compound can also be removed mechanically through pressure (the process of immersing the fly's body in water). This shows that the process of drowning aims to extract or release antimicrobial compounds from the digestive tract of flies to neutralize pathogenic bacteria that have mixed in the liquid in specific containers. This review aims to examine various reports related to antimicrobial substances produced in flies and their evidence in this hadith.Abstrak: Lalat rumah (Musca domestica) merupakan vektor pembawa bakteri penyebab penyakit karena kebiasaan hinggap dan makan pada berbagai substrat bakteri patogen. Perannya sebagai pembawa penyakit memiliki kontradiksi dengan hadist yang diriwayatkan oleh Bukhari yaitu “Jika seekor lalat jatuh ke bejana kamu, tenggelamkanlah kemudian singkirkan, karena salah satu sayapnya membawa penyakit dan sayap lainnya adalah obatnya”. Hadist ini mengindikasikan adanya senyawa antimikroba yang dihasilkan dari tubuh lalat. Berbagai laporan penelitian menunjukkan bahwa kebenaran hadist ini yaitu pada sayap lalat (kiri dan kanan) terdapat bakteri simbion penghasil antimikrob yang mampu membunuh bakteri patogen pada salah satu sayap atau keduanya. Senyawa antimikrob juga dihasilkan secara alami dalam pencernaan lalat sejak tahap larva hingga dewasa sebagai respon pertahanan tubuh terhadap keberadaan bakteri patogen ditubuhnya. Senyawa antimikrob tersebut berupa lisozim, defensin, cecrofin, diptericin dan beberapa senyawa peptida antimikrob. Senyawa ini juga dapat dikeluarkan secara mekanik melalui tekanan (proses penenggelaman tubuh lalat dalam air). Hal ini menunjukkan bahwa proses penenggelaman lalat kedalam air bertujuan untuk mengekstrak atau mengeluarkan senyawa antimikrob dari pencernaan lalat untuk menetralisir bakteri patogen yang telah bercampur dalam cairan di wadah tertentu. Review ini bertujuan untuk mengkaji berbagai laporan terkait senyawa antimikrob yang dihasilkan pada tubuh lalat dan pembuktiannya pada hadist tersebut.